2016
DOI: 10.1007/s12020-016-0910-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for elevated (LIMK2 and CFL1) and suppressed (ICAM1, EZR, MAP2K2, and NOS3) gene expressions in metabolic syndrome

Abstract: The metabolic syndrome (MetS) is a common multicomponent condition including abdominal obesity, dyslipidemia, hypertension, and hyperglycaemia. The aim of this study was to investigate the associations of the expression of a panel of signalling genes with the MetS in a Turkish population. A total of 54 MetS patients and 42 healthy controls with similar age and sex were included to this study. mRNA from blood samples was extracted, and real-time polymerase chain reaction was performed for gene expressions using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…This may highlight that the serological cellular adhesion molecules may be modifiable with 16 weeks of exenatide treatment whereas RH-PAT may require more time to show a significant change, and clarification of these functional findings with longer studies involving serial measurement of the serum endothelial markers are required. The correlation of decreased ICAM-1 with triglycerides and p-selectin with hip circumference is in accord with their relationship with metabolic syndrome and their reduction that reflected the weight loss (37, 38).…”
Section: Discussionsupporting
confidence: 55%
“…This may highlight that the serological cellular adhesion molecules may be modifiable with 16 weeks of exenatide treatment whereas RH-PAT may require more time to show a significant change, and clarification of these functional findings with longer studies involving serial measurement of the serum endothelial markers are required. The correlation of decreased ICAM-1 with triglycerides and p-selectin with hip circumference is in accord with their relationship with metabolic syndrome and their reduction that reflected the weight loss (37, 38).…”
Section: Discussionsupporting
confidence: 55%
“…The present study investigated epigenetic changes that occurred after nerve injury. Among the adhesion-associated differentially methylated genes identified in the present study, several important genes have been implicated in cell adhesion or proliferation, including Bcar1, Col5a3, Col18a1, Ezr, Col3a1 and Stat5a (59)(60)(61).…”
Section: Discussionmentioning
confidence: 76%
“…Generally, the positive association was due to three major mechanisms, including decreased testosterone, adipokine alterations and insulin resistance ( 2 , 16 ). Recently, several studies reported the involvement of ILK, β-parvin and cofilin in patients with obesity or metabolic syndromes ( 7 9 ). Meanwhile, a pioneering research conducted by Shibue et al firstly identified that the activation of ILK/β-parvin/cofilin pathway was critical in the formation of FLPs and the progression of carcinomas ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The researchers identified that the activation of integrin-linked kinase (ILK), β-parvin, cofilin pathway could promote caner progression, via enhancing the formation of FLPs and maintaining its existence, which raised a brand new perspective in cancer researches ( 6 ). Meanwhile, the signaling of ILK, β-parvin or cofilin were also involved in obesity and energy metabolism as recently proposed ( 7 9 ). Liu et al ( 7 ) discovered that oleic acid, with high levels in sera of obese patients, would activate ILK signaling pathway and therefore promote proliferation of renal cell carcinoma.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation